Ion Exchange Properties of Irradiated and Chemically Modified Clinoptilolite Regarding to Cs⁺ and Sr²⁺ - Akhalbedashvili, L.; Todradze, G.; Kekelidze, N.; Keheyan, Y.; Yeritsyan, G.; Gevorkyan, R. (Хімія, фізика та технологія поверхні, 2010)
The ion exchange sorption of Cs⁺ and Sr²⁺ on clinoptilolite (CL) from deposit of Armenia in initial, modified by e- and g-irradiation, decationated with a hydrochloric acid, and cation-contained forms was studied. On the basis of received data the exchange capacity Е for Sr²⁺ and Cs⁺, distribution factor Кd, sorption factor Кs were determined. It was shown that untreated CL(Ar), decationated CL(Ar)H and Cacontaining forms are characterized by a big ion exchange activity on strontium and cesium to compare with irradiated samples and the most perspective ion exchange sorbents for these ions are CL samples modified by a chemical way.